Nb3Sn Accelerator Magnets Designs, Technologies and Performance - Schoerling, Daniel; Zlobin, Alexander V. (Particle Acceleration and Detection, 2019)
This open access book is written by world-recognized experts in the fields of applied superconductivity and superconducting accelerator magnet technologies. It provides a contemporary review and assessment of the experience in research and development of high-field accelerator dipole magnets based on Nb3Sn superconductor over the past five decades. The reader attains clear insight into the development and the main properties of Nb3Sn composite superconducting wires and Rutherford cables, and details of accelerator dipole designs, technologies and performance. Special attention is given to innovative features of the developed Nb3Sn magnets. The book concludes with a discussion of accelerator magnet needs for future circular colliders. ; Broadens our understanding of design and performance limits of high-field Nb3Sn accelerator magnets for a future very high energy hadron collider Offers beginners a concise overview of the relevant design concepts for a new generation of superconducting accelerator magnets based on Nb3Sn superconductor Illustrates the complete process of accelerator magnet design and fabrication Provides a contemporary review and assessment of the past experience with Nb3Sn high-field dipole accelerator magnets Identifies the main open R&D issues for Nb3Sn high-field dipole magnets